Yeast for pentose fermentation: Isolation, screening, performance, manipulation, and prospects - Ceccato-Antonini, Sandra Regina; Codato, Carolina Brito; Martini, Cristina [UNESP]; Bastos, Reinaldo Gaspar; Tauk-Tornisielo, Sâmia Maria [UNESP] (Springer Nature, 2017)
The global demand for energy has led the research and the investments to use plant biomass to convert the sugars contained in this material into ethanol. The characteristics of the substrate and process have a strong impact on the choice of microorganisms to be used for fermentation of the sugars. In the most of feedstocks for ethanol production, the sugars containing five carbons (pentoses) are abundant. Naturally occurring yeasts that can use pentoses as carbon source have been isolated from the environment, and among them, Pichia stipitis is one of the most important species. However, some important characteristics needed in ethanol industry are high resistance to inhibiting compounds and high fermentation performance and, until this moment, none a single strain that gather these features has not been found naturally. Techniques of evolutionary engineering and genetic manipulation have been applied to introduce and select the required traits for pentose fermentation in Saccharomyces cerevisiae, the most employed yeast industrially. This chapter discusses the context of the microorganisms, especially the yeast group, in the fermentation of hemicellulosic substrates for bioethanol production regarding isolation, screening, performance, limitations, prospects, and state of the art, trying to contribute to the improvement of the global process of ethanol production.
Keywords: Ethanol; Fermentation; Hemicelluloses; Pentoses; Yeasts